Sentiment and Sunsets: Analysing Online Reviews of Kuta Beach in Bali - Bhaskara, Gde Indra; Sastrawan, I Gede Anom; Yudiastina, I Gusti Bagus Arya (E-Journal of Tourism; Volume 11 Number 1 (March 2024)DO - 10.24922/eot.v11i1.114486, 2024)
This study offers a thorough examination of online reviews to gain insights into visitor opinions and experiences at Kuta Beach, a renowned tourist attraction in Bali, Indonesia. Using advanced techniques in sentiment analysis and data analytics, the research investigates 3,726 online reviews from January 2016 until October 2023, carefully analysing the content and emotional tone of each review. The research indicates that Kuta Beach is generally well-regarded, with a median review rating of 5 and a mean sentiment polarity of 0.41. However, there are significant issues raised about cleanliness and overcrowding. Aspect-Based Sentiment Analysis (ABSA) has identified cleanliness and crowdedness as important factors that impact visitor satisfaction. The findings of the study indicate that it is vital to address these concerns in order to improve the visitor experience and maintain the beach's popularity. In addition, the research provides valuable suggestions for enhancing visitor satisfaction, including addressing overcrowding, improving cleanliness, and fostering connections with local communities to promote sustainable tourism development. This analysis not only offers a glimpse into current visitor experiences but also enhances our understanding of consumer sentiments in the age of the internet, which is crucial for effective tourism management and marketing strategies.